Pengaruh Inflasi dan Nilai Tukar Rupiah Terhadap Penerimaan Pajak Pertambahan Nilai (PPN) (Studi pada Kantor Wilayah Direktorat Jenderal Pajak Jateng II) Periode 2019-2023 - Anggi Rostiana Ambarwati; Rispanty (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Value Added Tax (VAT) is a tax imposed on the consumption of goods and services within the customs area. VAT contributions are considered important for state revenues because they are the second largest contributor to other types of tax after income tax by providing around 30% of tax revenues. The purpose of this research is to test and analyze the influence of inflation and the rupiah exchange rate on Value Added Tax (VAT) receipts. This research was conducted at the Central Java II Regional Office of the Directorate General of Taxes (DJP) in the period January 2019 to December 2023. The population of this research was the inflation rate in Central Java and the rupiah exchange rate against one US dollar based on the selling rate. The data used in this research is monthly data so that 60 observations were obtained.  The sampling technique uses a saturated sample technique. Data analysis techniques use descriptive analysis, Classic Assumption Test, Multiple Linear Regression, Hypothesis Testing, and Determinant Coefficient (R2). The research results prove that there is a significant influence of inflation on Value Added Tax (VAT) revenues, while there is no significant influence on the Rupiah Exchange Rate on Value Added Tax (VAT) revenues.